Morphological and Molecular Identification of Tropical Bed Bugs From Two Cities of the Pearl River Delta in China. Issue 1 (2nd August 2020) - Zhang, Jingsheng; Xia, Yanwei; Wang, Changlu; Han, Dongliang; Ren, Dongsheng; Zheng, Jun; Xu, Xu; He, Yurong; Wang, Desen
Abstract: From the 1960s to the 1980s, with the implementation of nationwide 'Four-Pest Elimination' campaigns (bed bugs, Cimex lectularius L. and Cimex hemipterus (F.) (Hemiptera: Cimicidae), were listed as one of the targeted pests), bed bug infestations were gradually eliminated in most provinces in China. However, during the last two decades, reports of bed bug infestations in the Pearl River Delta of China have shown an upward trend. Up to now, the bed bug species occurring in this area was much less frequently reported. In this study, we used both morphological and molecular methods to accurately identify the species of bed bugs collected from the cities of Guangzhou and Foshan, China. Results indicated that no significant difference was observed in the mean pronotum width-to-length ratio of Guangzhou (2.6) and Foshan (2.4) specimens; however, both were significantly lower than that of a laboratory strain C. lectularius (3.1). The genetic distances of our specimens with C. hemipterus and C. lectularius were 0–0.2% and 22.2–22.6%, respectively. On the basis of the morphological characteristics and mitochondrial DNA sequence data, it can be affirmed that bed bugs collected from Guangzhou and Foshan were C. hemipterus .